2014
DOI: 10.4103/1673-5374.130094
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting sensory and motor recovery after the repair of upper limb peripheral nerve injuries

Abstract: OBJECTIVE:To investigate the factors associated with sensory and motor recovery after the repair of upper limb peripheral nerve injuries.DATA SOURCES:The online PubMed database was searched for English articles describing outcomes after the repair of median, ulnar, radial, and digital nerve injuries in humans with a publication date between 1 January 1990 and 16 February 2011.STUDY SELECTION:The following types of article were selected: (1) clinical trials describing the repair of median, ulnar, radial, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(25 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…Clinical reports have suggested that optimal functional recovery is dependent upon a sufficient number and quality of axons reaching their target within 1 year following injury [15][16][17][18]. After this time period, functional outcomes are poor [18][19][20]. This same pattern of strong initial regeneration potential followed by declining regenerative capacity during chronic denervation and poor functional outcomes from repair of proximal injuries suggests that the basic biology is likely to be comparable between rodents and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical reports have suggested that optimal functional recovery is dependent upon a sufficient number and quality of axons reaching their target within 1 year following injury [15][16][17][18]. After this time period, functional outcomes are poor [18][19][20]. This same pattern of strong initial regeneration potential followed by declining regenerative capacity during chronic denervation and poor functional outcomes from repair of proximal injuries suggests that the basic biology is likely to be comparable between rodents and humans.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Additionally, age plays a role in nerve plasticity and regaining function. Younger age has been associated with increased recovery due to children’s increased regenerative capabilities, with children having faster recovery times (mean of 18 months) compared with adults (average of 30–39 months) for peroneal nerve repairs.. 4 , 5 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…Despite early diagnosis and accurate nerve repair with modern surgical techniques, functional recovery never reached the preinjury level. Poor outcomes result from factors both intrinsic and extrinsic to the nervous system, such as the type and level of injury, integrity of the surrounding tissues, the timing of the surgery, and changes in spinal cord neurons and end organs [ 5 7 ]. Misdirection of regenerating axons at the injury site is still a major problem.…”
Section: Introductionmentioning
confidence: 99%